A real-life treatment cohort of pancreatic neuroendocrine tumors: High-grade increase in metastases confers poor survival - Zhang, Wu-Hu; Gao, He-Li; Liu, Wen-Sheng; Qin, Yi; Ye, Zeng; Lou, Xin; Wang, Fei; Zhang, Yue; Chen, Xue-Min; Chen, Jie; Yu, Xian-Jun; Zhuo, Qi-Feng; et al. (Frontiers in Endocrinology, 2022)
Background Tumor grade determined by the Ki67 index is the best prognostic factor for pancreatic neuroendocrine tumors (PanNETs). However, we often observe that the grade of metastases differs from that of their primary tumors. This study aimed to investigate the frequency of grade changes between primary tumors and metastases, explore its association with clinical characteristics, and correlate the findings with the prognosis. Methods Six hundred forty-eight patients with pancreatic neuroendocrine neoplasms treated at Fudan University Shanghai Cancer Center were screened for inclusion, and 103 patients with PanNETs who had paired primary tumors and metastases with an available Ki67 index were included. Re-evaluation of Ki67 was performed on 98 available samples from 69 patients. Results Fifty cases (48.5%) had a Ki67 index variation, and 18 cases (17.5%) displayed a grade increase. Metachronous metastases showed significantly higher Ki67 index variation than synchronous metastases (P=0.028). Kaplan–Meier analyses showed that high-grade metastases compared to low-grade primary tumors were significantly associated with decreased progression-free survival (PFS, P=0.012) and overall survival (OS, P=0.027). Multivariable Cox regression analyses demonstrated that a low-grade increase to high-grade was an unfavorable and independent prognostic factor for PFS and OS (P=0.010, and P=0.041, respectively). Conclusions A high-grade increase in metastases was an unfavorable predictor of PanNETs, which emphasized the importance of accurate pathological grading and could provide a reference for clinical decision-making.